2021
DOI: 10.1093/ckj/sfab022
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in patients after kidney transplantation

Abstract: Kidney transplantation is the treatment of choice for patients with end-stage renal disease. Next to the risk of allograft failure, major obstacles for disease-free survival after kidney transplantation comprise a higher incidence of cancers, infection, and cardiovascular (CV) events. Risk factors for adverse clinical outcomes comprise pre-existent comorbidities, the introduction of an immunodeficient status, as well as (lack of) lifestyle changes after transplantation. Indeed, physical inactivity and poor phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 89 publications
1
20
0
1
Order By: Relevance
“…There is now emerging evidence that a sedentary lifestyle can be associated with an increased risk of cardiovascular events, a major cause of morbidity and mortality after KT [ 82 , 83 , 84 , 85 ]. On the other hand, regular exercise and physical activity may reduce the burden of cardiovascular risk factors and improve the perceived health status and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…There is now emerging evidence that a sedentary lifestyle can be associated with an increased risk of cardiovascular events, a major cause of morbidity and mortality after KT [ 82 , 83 , 84 , 85 ]. On the other hand, regular exercise and physical activity may reduce the burden of cardiovascular risk factors and improve the perceived health status and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Especially developing adapted interventions and use of specific implementation strategies can support to reach these patients and to get and keep them more physically active. RCTs show a bias towards inclusion of more physically active patients or patients willing to engage in physical activity [ 62 , 63 ]. Also in Transplantoux this has been the case, resulting in a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that psychomotor activity could provide an effective support tool for school learning. References ESERCIZIO, PREVENZIONE E TERAPIA 3 31 Interrelationship among thigh intermuscular adipose tissue, cross-sectional area, muscle strength and functional mobility in older subjects…”
Section: Discussionmentioning
confidence: 99%